Astrocytic release of ATP through type 2 inositol 1, 4, 5‐trisphosphate receptor calcium signaling and social dominance behavior in mice. (21st July 2020) - Guillot de Suduiraut, Isabelle; Grosse, Jocelyn; Ramos‐Fernández, Eva; Sandi, Carmen; Hollis, Fiona
Abstract: Brain mitochondrial function is critical for numerous neuronal processes. We recently identified a link between brain energy and social dominance, where higher levels of mitochondrial function resulted in increased social competitive ability. The underlying mechanism of this link, however, remains unclear. Here, we investigated the contribution of astrocytic release of adenosine triphosphate (ATP) through the type 2 inositol 1, 4, 5‐triphosphate receptor to social dominance behavior. Mice lacking the type 2 inositol 1, 4, 5‐triphosphate receptor were characterized for their social dominance behavior, as well as their performance on a nonsocial task, the Morris Water Maze. In parallel, we also examined mitochondrial function in the medial prefrontal cortex, nucleus accumbens, and hippocampus to investigate how deficiencies in astrocytic ATP could modulate overall mitochondrial function. While knockout mice showed similar competitive ability compared with their wild‐type littermates, dominant knockout mice exhibited a significant delay in exerting their dominance during the initial encounter. Otherwise, there were no differences in anxiety and exploratory traits, spatial learning and memory, or brain mitochondrial function in either light or dark circadian phases. Our findings point to a marginal role of astrocytic ATP through IP3 R2 in social competition, suggesting that, under basal conditions, the neuronal compartment is predominant for social dominance exertion. Abstract : The role of astrocytic ATP was investigated in social dominance using IP3 R2 KO mice. We found no differences between IP3 R2 KO and WT mice in behavior or mitochondrial function. Astrocytic ATP signaling through IP3 R2 has a minimal role in social dominance behavior.